C. McGinn. A Deontological Theodicy / trans. from Engl. V. A. Sergeeva - V. A. Sergeeva (Омский научный вестник: Серия "Общество. История. Современность")
The essay examines the inconsistence problem of the existence a perfect God and evil in the world. It contains criticism of the traditional view that the concept of God as a morally perfect entity is paradoxical. Essay is demonstrated that such views are based on an extreme form of utilitarianism. It is argued that the idea of God and evil coexisting in the world is not inconsistent if we accept the deontological view in ethics that the general obligation to eliminate suffering wherever it occurs cannot be one’s moral duty. It is proved that the idea of the coexistence of God and evil in the world does not contain a contradiction if we accept the deontological point of view in ethics that the obligation to eliminate suffering wherever it occurs cannot be anyone’s moral duty.